Portal Transaksi Barang Secara Online Dengan Fitur Penanganan Permintaan Barang Tidak Tersedia - I Ketut Adi Wicaksana; Daniel Jahja Surjawan (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
In the era of development technology, there are so many people who have not been able to use it. For examples to make a sale and purchase transaction they are using conventional way where the customers must go to the seller's place, but the problem comes when the customers do not get the item they are needed. Another problem is that conventional seller financial statements are still records in a paper that can be lost or scattered, and sometimes customers want to find items that are needed but not in any list of stores that cause wasting customer’s time and energy and ineffective. This research will make a portal that can manage the transaction for sellers and customers. For reporting, a feature will be made that shows the description and availability of stock items, as well as digital financial records for sellers as financial statements. This research is different from other e-commerce webs, where the special feature added is to manage the customer goods request that is not available as a service to ensure customers satisfaction.